Breadmaking with an old wholewheat flour: Optimization of ingredients to improve bread quality. (March 2020) - Parenti, Ottavia; Guerrini, Lorenzo; Cavallini, Benedetta; Baldi, Fabio; Zanoni, Bruno
Abstract: Processing strategies are necessary to improve the quality of baked old wholewheat flour products, since they are required by consumers but have poor technological properties. The present study tested the addition of common improvers on an old wholewheat flour performance to optimize bread quality. At first, the effect of seven improvers on dough rheology and bread specific volume was evaluated using a screening design method. All of the improvers affected the farinographic parameters; the most promising effects were shown by sucrose, salt and guar gum. Bread specific volume was significantly improved by sucrose, extra virgin olive oil and ice; hence, the effects of these variables on dough rheology and bread quality were evaluated in-depth in a full factorial trial. Dough stability and dough weakening were significantly improved by sucrose and extra virgin olive oil. Sucrose and extra virgin olive oil interaction optimized bread specific volume, crumb specific volume and hardness. The addition of 2% sucrose and 3% extra virgin olive oil resulted in optimized bread, on which a qualitative sensory evaluation was performed. This optimization approach could be applied to other wholewheat flours to improve product quality, hence promoting the consumption of high nutritional value breads. Highlights: Two trials (T1, T2) tested common bread improvers on an ancient wholewheat flour. Salt, sucrose and guar gum improved dough rheology in the fractional trial (T1). Sugar, extra virgin olive oil and ice increased bread specific volume in T1. A full factorial trial (T2) was performed to optimize bread quality. 2% sucrose and 3% extra virgin olive oil gave the best bread quality.